Die Grossen Seen Nordamerikas - Keller, Reiner (ERDKUNDE, 1959)
According to their origin and morphology, the Great Lakes may well be likened to the Baltic Sea. On the other hand, rapids and waterfalls cut them off from the influence of the ocean, whereas the Baltic has become a tributary sea. Because of their being the largest continuous fresh water surface on earth and their relatively small catchment areas, the Great Lakes are especially suited for water cycle studies. The paper investigates level changes for the individual lakes for the period from 1860 to 1956, both by annual values over long periods and as regards changes over the years, depending on climatic oscillations. It appears that the amount of water discharged from the Great Lakes has declined during recent decades (table 8). The water cycle was calculated for the individual lakes and for the Great Lakes as a whole (table 5); the influence the different climatic locations is emphasised. While it was possible to calculate the annual values of precipitation, discharge, and evaporation, this could not be done for the individual months because of lack of sufficient data about the regime of the tributary rivers and the annual course of evaporation (the percentage per month). There are obviously no such direct connexions between the average monthly lake levels and the average monthly discharge that the monthly cycle could have been calculated on this basis. The complicated monthly cycles, without the evaporation data, are shown in table 6 and figure 3. The level changes, be they natural or human conditioned, have their bearing on hydro-electric power utilisation and shipping within the area of the Great Lakes. Because of the shallowness of the Rivers which link the lakes with each other only part of the available tonnage of the cargo fleet of the lakes can be utilised to the full. Despite this, shipping within the Great Lakes has lately overtaken that of the Suez and Panama canals. In this connexion the importance of the Great Lake -St. Lawrence Deep Waterway is emphasised.